Pengaruh Cuaca Berawan terhadap Pengeringan Kelapa Kukur sebagai Bahan Kelapa Gongseng dengan Sistem Solar Drying - Dinni Agustina; Ratna Sary; Muhammad Iqbal (Jurnal Teknik Mesin Unsyiah, 2014)
Dessicated coconut is the main ingredient in the manufacture of coconut ‘gongseng’ spices. Traditional methods of drying the grated cocont directly in the sun have constraints such as relatively longer drying time, products hygiene and supervisory personnel. Solar dryers conditioning system with a solar collector has been developed to overcome these constraints and tested in Lamlhom area, Aceh Besar. The research objective was to determine the effect of cloudy weather on the performance of solar drying system in term of the moisture content and the qualityof the ddessicated coconut. Tests carried out in the temperature range of 30°C - 60°C in a state of clear and cloudy weather. Tests comparing the two samples of coconut grater with a weight of 2 kg and 4 kg at two weather condition;sunny and cloudy. The experimental results of both samples on sunny and cloudy weather conditions indicate that the water content of the coconut water is still in the range of moisture content standards set by SNI 01-375-2000 which is maximum moisture content of 3%.